1990
DOI: 10.1002/aja.1001870308
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of histogenesis in the bursal lymphoid follicle of the chicken

Abstract: The development of the bursal follicle and the appearance of the follicle-associated epithelial (FAE) cell and the reticuloepithelial (REp) cell were studied. The stages of development of the bursal follicle were observed by light and electron microscopy; an anticytokeratin monoclonal antibody was also used. At the beginning of follicle development, a mesenchymal cell cluster is observed in the tunica propria; the cluster becomes wedged in a niche of the surface epithelium, and gradually it is completely surro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…22,23) It is thought to play an important role in allowing the antigen to enter into the lymphoid follicle and excluding foreign substances from the lymphoid follicle, but the detailed of the function of FAE at the molecular level are largely unknown. 13,14) However, it has been reported that the entry of foreign substances into the BF is necessary to the acquisition of antibody diversity.…”
Section: Discussionmentioning
confidence: 99%
“…22,23) It is thought to play an important role in allowing the antigen to enter into the lymphoid follicle and excluding foreign substances from the lymphoid follicle, but the detailed of the function of FAE at the molecular level are largely unknown. 13,14) However, it has been reported that the entry of foreign substances into the BF is necessary to the acquisition of antibody diversity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the FAE cells are epithelial cells (Schaffner et al, 1974a;Schaffner et al, 1974b;Davenport and Allen, 1995;Paramithiotis and Ratcliffe, 1996), which are positive (Viamontes et al, 1989), or weakly positive (Olah and Glick, 1992) to anti-cytokeratin antibodies. Other authors reported that they are mesenchymal cells (Dolfi et al, 1981;Lupetti et al, 1983Lupetti et al, , 1986Lupetti et al, 1990), that are negative to anti-cytokeratin . Olah et al (2001) and Nagy et al (2001) found that the monoclonal antibodies to GIIF3 and NIC2, which are able to recognize mesenchymal elements, were expressed by FAE cells and cortico-medullary cells.…”
Section: Plical Epitheliummentioning
confidence: 97%
“…The reticular-epithelial cells detected during embryonic development (Jolly, 1914;Ackerman and Knouff, 1959;Ackerman, 1962;Lupetti et al, 1990) or in adult life (Frazier, 1974;Glick, 1983;Houssaint et al, 1986;Eerola et al, 1987;Dolfi et al, 1990;Olah and Glick, 1992) have been described by ultrastructural studies (Frazier, 1974) and classified as pale, dark and intermediate cells. These cells had cytoplasmic processes which were often connected to the adjacent epithelial cells forming a supporting network for the lymphocytes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The mucosa contains several plications and a large number of polyhedral lymphoid follicles [8], composed of cortex, medulla and corticomedullary border [9,10]. The surface comprised two kinds of epithelium: follicle associated epithelium (FAE) covering the apex of each lymphoid follicle and the interfollicular epithelium (IFE) covering the space between the lymphoid follicles [3,11].…”
Section: Introductionmentioning
confidence: 99%